2019
DOI: 10.2134/agronj2019.04.0309
|View full text |Cite
|
Sign up to set email alerts
|

An Inverse Correlation between Corn Temperature and Nitrogen Stress: A Field Case Study

Abstract: Nitrogen is one of the most important yield‐limiting nutrients for corn (Zea mays). The ability of thermal remote sensing to detect nitrogen deficiency in corn may enable precision agriculture to modify nitrogen rates according to field conditions. This study applies the exergy destruction principle as a theory to explain the inverse relationship between surface temperature and nitrogen rate. Two hypotheses were developed. First, it was hypothesized that agricultural crops experiencing greater growth and provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Yan et al [42] found that rice canopy temperature responded to N rate, with N stress causing higher temperatures. Similarly, Alzaben, Fraser, and Swanton [22] used thermal imagery to investigate the relation between canopy temperature and N status. The study observed that both corn leaf and whirl temperatures statistically responded to N treatment, with optimal N corresponding to lower canopy temperature.…”
Section: Diagnosis Of In-season N Status Using Nnimentioning
confidence: 99%
See 1 more Smart Citation
“…Yan et al [42] found that rice canopy temperature responded to N rate, with N stress causing higher temperatures. Similarly, Alzaben, Fraser, and Swanton [22] used thermal imagery to investigate the relation between canopy temperature and N status. The study observed that both corn leaf and whirl temperatures statistically responded to N treatment, with optimal N corresponding to lower canopy temperature.…”
Section: Diagnosis Of In-season N Status Using Nnimentioning
confidence: 99%
“…These additional metrics can be used to calculate physiological metrics such as fractional PAR (fPAR) and canopy-air temperature difference (∆Temp). Previous research indicated that PAR [21] and canopy temperature [22] could be used to estimate biomass and crop N stress. Therefore, through measuring spectral, estimated structural characteristics, and climatic variables, the Crop Circle Phenom sensor system is hypothesized to be able to improve corn N status estimation and diagnosis compared to only using vegetation indices such as NDVI and NDRE.…”
Section: Introductionmentioning
confidence: 99%
“…The second canonical pair explains that the increase in the content of the amino acids Alanine (ALA), Arginine (ARG), Asparagine (ASP), Proline (PROL), Serine (SER), Tryptophan (TRYP) and Methionine (MET), are correlated to reduction of the seed length (SL) and seed thickness (ST) components. This situation can be explained by nitrogen deficiency, given that this element is a component of the structure of amino acids, as well as, emphasizes Alzaben, Fraser and Swanton (2019), by stating that nitrogen is one of the most important nutrients to limit corn yield, and supported by Cates and Ruark (2017) with decreases in the yield of Poaceae due to the reduction of the organic matter content of the soil and consequently the supply of nitrogen. Positive correlation of the amino acids alanine (ALA), asparagine (ASP), serine (SER), tryptophan (TRYP) and methionine (MET), was verified with the components of the yield ear mass (EM), ear grain mass (EGM), seed thickness (ST) and grain yield (GY), in the third canonical pair.…”
Section: Figurementioning
confidence: 99%
“…Furthermore, the thermal camera was calibrated under laboratory conditions, using a blackbody source (463 cavity black-body, Infrared industries, Hayward, CA, USA) with a 2.2 cm diameter selected measurement aperture. The difference between the temperature obtained by the thermal camera and the temperature obtained by using the black-body cavity was no more than the accuracy of the thermal camera (±2 • C) [63]. The sample size for each experiment was randomly selected as 10 corn plants in the middle two rows out of 30 plants per bench, to avoid border effects.…”
Section: Thermal Image Acquisition and Processingmentioning
confidence: 99%